2015
DOI: 10.1111/jmi.12265
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing use of the structural chemical analyser (variable pressure FESEM‐EDX raman spectroscopy) on micro‐size complex historical paintings characterization

Abstract: The novel Structural Chemical Analyser (hyphenated Raman spectroscopy and scanning electron microscopy equipped with an X-ray detector) is gaining popularity since it allows 3-D morphological studies and elemental, molecular, structural and electronic analyses of a single complex micro-sized sample without transfer between instruments. However, its full potential remains unexploited in painting heritage where simultaneous identification of inorganic and organic materials in paintings is critically yet unresolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Both processes provide spaces that facilitate resin infiltration and suitable bonding between the resin and tooth. When nano-HA solution was used, the ionic form of Ca and P enters the porous enamel and provides seeds for remineralization [25, 28, 34, 35]. SEM images in the present study showed differences between groups in the degree of penetrations of the resin sealant into these spaces.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Both processes provide spaces that facilitate resin infiltration and suitable bonding between the resin and tooth. When nano-HA solution was used, the ionic form of Ca and P enters the porous enamel and provides seeds for remineralization [25, 28, 34, 35]. SEM images in the present study showed differences between groups in the degree of penetrations of the resin sealant into these spaces.…”
Section: Discussionmentioning
confidence: 59%
“…Energy dispersive X-ray spectroscopy is a chemical elemental microanalysis technique to measure mineral content at the ultrastructural level, and has been used to investigate the remineralization capacity of different materials [14, 17, 24]. In the present study we used FESEM instead of SEM to obtain more detailed structural data of higher quality and resolution [35]. Our analysis of EDS data focused on changes in Wt% of Ca, P and the Ca/P ratio, given that these ions are important indicators of the effect of nano-HA on enamel remineralization.…”
Section: Discussionmentioning
confidence: 99%
“…An additional light source and a camera serve for illuminating and viewing of the sample for the sake of correlation between the region imaged with the SEM and the same ROI for Raman. Since the objective lens is parallel to the electron column, Raman measurement can be performed without any intensity or resolution loss contrariwise to the “on‐axis” setup, where the restrictions of the optics due to the SEM pole piece lead to a diminished Raman signal and resolution, which may handicap analysis . The controlling software Control FIVE from WITec enables the collection of single spectra and additionally enables Raman mapping which means imaging with Raman information in each pixel.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, for performing simultaneous elemental analysis using X-rays, these hyphenated instruments can have an X-ray spectrometer connected to the SEM, making the technique SEM-EDX/Raman. Guerra and Cardell 2015). Figure 14a shows the study by de la Fuente et al (2016) where the different rust morphologies very close to each other like globular formations (A), thin laminas in the form of flower petals, bird nests or honeycombs (B), and thick laminas in the form of worm nests (C) were imaged by SEM and the integrated Raman set-up was used to get the corresponding Raman spectra from these three areas (Figure 14b-d).…”
Section: Scanning Electron Microscopy (Sem)-ramanmentioning
confidence: 99%